Investigating the corrosion resistance of copper-ruthenium coatings - Zaba, Winnie (My University, 2018)
Copper has been widely used, and its increased application in different industries resulted in high demands. With more applications, it has increased the need to improve the mechanical, and corrosion properties to improve its life span during operation. Pure copper has been used in many aqueous environments (e.g. pipe lines, storage tanks, and electro-winning) because of its good conductivity and corrosion resistivity. However, when it is exposed to harsh environmental conditions with high acidity it experiences corrosion. This research focuses on these corrosion characteristics. Appropriate surface chemistry is very important in many of the copper applications. Surface engineering techniques have been applied to improve the corrosion property of many materials like stainless steel, but only a few scientific investigations and developments have been done on copper. This development has been carried out by introducing ruthenium to the copper surface to improve the corrosion resistance and serviceability of copper in general. The ruthenium was added to the copper surface using thermal spray coating high velocity oxygen fuel spray coating, cold spray coating, spark plasma sintering, and electroplating. One should note that the nature of the surface coating and arrangement of the powder particles determines the overall protection that can be achieved/induced. For the different coatings and alloys, ruthenium was added in 0.5, 1, and 2 weight percent. This research found that in many cases, the corrosion resistance increased with increase in ruthenium content. The HVOF and SPS experienced the same trend. The CSC coating did not achieve any corrosion resistance improvement when compared to as-received copper. The electroplating of a copper substrate successfully decreased the corrosion rate in sulphuric acid at 65°C. The electroplated powders had contaminations that affected the corrosion characteristics of the coating and the alloy. Other properties of the material were also affected after the ruthenium addition. These also include the hardness of the materials which was increased with the increase in ruthenium content. The research limitations encountered was the shortage of equipment to perform other tests like the scratch adhesion test which would have validated the adhesion property of the coatings.
A dissertation submitted in fulfilment of the requirements for the degree of Masters of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, 2018
Keywords: Corrosion and anti-corrosives; Metal coating; Electrolytic corrosion